Xeroderma Pigmentosum with Severe Neurological Manifestations/De Sanctis–Cacchione Syndrome and a Novel XPC Mutation (2017)
ABSTRACT: Several genetic disorders caused by defective nucleotide excision repair that affect the skin and the nervous system have been described, including Xeroderma Pigmentosum (XP), De Sanctis–Cacchione syndrome (DSC), Cockayne syndrome, and Trichothiodystrophy. Cutaneous photosensitivity with an increased risk of skin malignancy is a common feature of these disorders, but clinical manifestations commonly overlap these syndromes. Several genes have been found to be altered in these pathologies, but we lack more genotype-phenotype correlations in order to make an accurate diagnosis. Very few cases of DSC syndrome have been reported in the literature. We present a case of a 12-year-old Colombian male, with multiple skin lesions in sun-exposed areas from the age of 3 months and a history of 15 skin cancers. He also displayed severe neurologic abnormalities (intellectual disability, ataxia, altered speech, and hyperreflexia), short stature, and microcephaly, which are features associated with DSC. Genetic testing revealed a novel germline mutation in the XP-C gene (c.547A>T). This is the first case of an XP-C mutation causing De Sanctis–Cacchione syndrome. Multigene panel testing is becoming more widely available and accessible in the clinical setting and will help rapidly unveil the molecular etiology of these rare genetic disorders.